(3GdEjVGM aj TQM ebGeGJ GdMQjQjs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s; (3GdMQjQj,J (B516 (3g` s ((3YHOGdZahQ Hf eMeO GdLhgQj s)
(3ChdgG (B:s
(3hHYO , aEfi de CQ aj cJH GdYQHjI hGdGOH , hdGai JUGfja GdYLe hGdYQH cJGH CMSf JCdjakG ef GdebGeGJ GdJi CfTCgG GdMQjQi aCQOJ Cf GNhV ai YHGHg hCQhV dHYV WdGHg s
(3BNQgG (B:s
(3acd ef SeY HGSeg , hXaQ HhSeg , hVYg Ydi beI GdQhGL , hJbHdg HbHhd MSf heG GfS CfS ehdGi GdUOQ GdcHjQ GdYdGeI Sbi Gddg GdMQjQi TBHjH QVhGfg, hcSGg LdGHjH ZaQGfg s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs